"Opening the Eyes of Memory: War Painting in Adriano Sousa Lopes and Amadeo de Souza-Cardoso", in Personal Narratives, Peripheral Theatres: Essays on the Great War (1914–18) - Amado, Maria Teresa (2018)
After a hundred years, when we open the eyes of memory with pho- tographs, drawings and paintings of the Great War, it is impossible not to feel the horror of war. Beyond recording events and allowing us to remember them, what is the purpose of the art of the period? How can we bring to life a war which became a huge generalized massacre, a mechanical war with tanks, artillery, gas, airplanes and submarines, hidden and without a face, with no clear goals? During the con- flict, war not only lost its traditional iconography—the horse, the flag, the soldier, the hero—but even the traditional “language” of painting struggled to express the states of light and movement, of speed and noise, of pieces of flying metal and fragmentation. It is in this context that this article seeks to compare the artistic and iconographic language of Sousa Lopes and Amadeu Sousa Cardoso. In Sousa Lopes, an official war artist working in the trenches of Flanders, the horror and the absurdity of the unnatural violence is expressed in a figurative and realistic way. In Amadeu Sousa Cardoso, the language is contemporary and abstract, as well as profoundly original in aesthetic, conceptual and artistic terms. In his war paintings, and above all in the painting titled “Entrada”, Amadeu, twenty years before Picasso, shows how war leads to the destruction of life, harmony and the Light. In the perversity of war, electric light, traditionally a symbol of modernity, becomes something unnatural.